Cauda equina syndrome after spinal tetracaine: Electromyographic evaluation-20 years follow-up - Vianna, PTG; Resende, LAL; Ganem, Eliana Marisa [UNESP]; Gabarra, Roberto Colichio [UNESP]; Yamashita, Seizo [UNESP]; Barreira, A. A. (Lippincott Williams & Wilkins, 2001)
CAUDA equina syndrome (CES) has long been recognized as a rare complication of spinal anesthesia.(1) CES has been described after administration of spinal anesthetics with lidocaine(2) and bupivacaine.(3) In 1991,(4) CES was reported after continuous spinal anesthesia with 1% tetracaine. In 1980, at our university hospital, six adult female patients underwent perineal gynecologic surgery using a spinal anesthetic of 2 ml tetracaine, 1.2%, in 10% glucose. The concentration of the injected tetracaine was unknown by the anesthetists. In all cases, lumbar puncture was performed at the L3-L4 interspace with a disposable spinal needle while the patients were in the sitting position. CES was first diagnosed 72 h or later postoperatively; previous diagnosis was not possible because patients had an indwelling urethral catheter. The diagnosis of CES was confirmed in all patients. During the past year, after institutional approval and informed consent, clinical, magnetic resonance imaging, electromyographic examinations, and conduction studies were performed in three of the above patients. Examinations were not possible on the other three patients because one had recently died, another could not be located, and the third refused to participate. T1 and T2 magnetic resonance image readings were obtained with Gadolinium contrast from a 0.5 Tesla General Electric apparatus (General Electric, Tokyo, Japan). Bilateral sensory and motor conduction studies of the sciatic nerve branches were obtained using a two-channel Nihon-Kohden Neuropack 2 (Nihom-Kohden Corporation, Tokyo, Japan). Electromyography was performed in accordance with conventional techniques.(5,6)